Effect of temperature and other factors on plastics and elastomers - McKeen, Laurence W. (Plastics Design Library/William Andrew, 2008)
Most plastic products and parts are expected to perform in environments other than at room temperature and standard humidity conditions. The Effect of Temperature and Other Factors on Plastics and Elastomers is an exhaustive compilation of multipoint performance data of plastics as they are exposed to varying temperature and humidity conditions. The second edition of this much used reference book is an extensive upgrade from the original 1991 publication. Additional plastics families have been added, obsolete products have been removed and replaced, approximately two thirds of the graphs are new, and all tables have been completely revised and contain extensive additional data